Effects of Methanol Extract of Illicium verum Hook.f on Coagulation Parameters in Rabbits - Hafiza Tuseef Sayyar; Muhammad Liaquat Raza; Tahira Assad Shaikh (ziauddin University, 2020)
Background: Chinese Star anise is known as Illicium verum hook.f; a distinguished spice utilized in dishes, especially in the Asian region. However, it was not evaluated for its anticoagulant potential. The study was designed specifically to evaluate the effect of methanol extract of Illicium verum hook.f on various coagulation parameters in animal models. Methods: In the study, effect of methanol extract of I. verum hook.f was evaluated on various coagulation parameters such as Prothrombin time (PT), activated partial thromboplastin time (aPTT) and thrombin time (TT) in rabbits at three different doses, i.e. 150, 250 and 350 mg/kg body weight after 60 days of continuous dosing. Comparison was also done with the standard anticoagulant drug i.e., Warfarin. Data was compared with control group's values by One-Way ANOVA trailed by post hoc Tukey's test. Results: The current analysis revealed that administration of methanol extract of I. verum hook.f at 250 mg of dose for 30 days resulted in elevation of PT, aPTT and TT, whereas, highly significant increase was observed in PT and aPTT at the 350 mg/kg. However, administration of the extract for 60 days at 250 mg/ kg resulted in significant increase in PT while, significant increase in aPTT. Administration at 350 mg/kg of dose for same period resulted in significant rise in PT and aPTT in contrast to TT. Conclusion: Methanol's extract of I. verum hook.f (star anise) showed significant anticoagulant effects, which is important in hypercoagulable conditions and cardiovascular diseases. However, isolation and identification of active ingredients is required to further validate the results.